Сomparative evaluation of different soy protection schemes - Sergienko, V.; Shita, O. (Quarantine and plant protection, 2022)
Goal. Evaluate the effectiveness of various soybean protection schemes using preventive measures for seedlings and control measures during the growing season. Methods. Field, phytopathological, herbological, mathematical and statistical. According to the first protection scheme, the seeds were treated comprehensively with Maxim XL 035 FS (fludioxonil, 25 g/l + metalaxyl-M, 10 g/l) fungicide, 0.5 l/t, Taboo s.c. (imidacloprid, 500 g/l) insecticide, 0.5 l/t and Biomag-Soya (Bradirhizobium japonicum) biological product, village, 2.5 l/t. Harnes c.e. (acetochlor, 900 g/l), herbicide was applied during sowing with a consumption rate of 2.0 l/ha. According to the second scheme during the growing season herbicides Bazagran, l.c. (bentazone, 480 g/l) with a rate of 2.5 l/ha and Panther, c.e., 1.0 l/ha (quizalofop-P-tefuril, 40 g/l) in the phase of 3—4 true leaves in culture. Against diseases in the budding phase — the beginning of flowering and at the beginning of bean formation was sprayed with fungicide systemic contact action Amistar Extra 280 SC (cyproconazole, 200 g/l + azoxystrobin, 80 g/l), 0.75 l/ha. The quantitative and species composition of weeds in the experimental plots, the infestation of phytopathogens of soybean plants, the effectiveness of drugs in various protection schemes, crop yield were determined. Results. Both protection schemes effectively controlled weed infestation and disease. The first protection scheme proved to be more effective against dicotyledonous weeds: the effectiveness 60 days after herbicide application was 95.4% versus 82% according to the second scheme. Cereal weeds were more effectively controlled during the growing season. Protection of soybeans against Alternaria was almost equally effective in both schemes. Soybean downy mildew more effectively limited fungicidal treatments during the growing season. Under both protection schemes, soybeans yielded significantly higher yields than controls. However, yields, number of beans per plant and weight of 1000 grains were higher in the first scheme compared to the second protection scheme. Conclusions. Both protection schemes provided high weed and disease control rates during the soybean growing season. Differences in the control of different biological groups of weeds and different types of diseases are obviously related to the peculiarities of the use and toxic effects of the drugs used. However, the application of a system of preventive protection measures can reduce the pesticide load on the agrocenosis and limit the negative impact of pesticides on soybean plants during the growing season.